Plasmodium falciparum transcription factor AP2-06B is mutated at high frequency in Southeast Asia but does not associate with drug resistance - Qiyang Shi; Changhong Wang; Wenluan Yang; Xiaoqin Ma; Jianxia Tang; Jiayao Zhang; Guoding Zhu; Yinlong Wang; Yaobao Liu; Xiaoqin He (Frontiers in Cellular and Infection Microbiology)
IntroductionA continuing challenge for malaria control is the ability of Plasmodium falciparum to develop resistance to antimalarial drugs. Members within the Plasmodium transcription factor family AP2 regulate the growth and development of the parasite, and are also thought to be involved in unclear aspects of drug resistance. Here we screened for single nucleotide polymorphisms (SNPs) within the AP2 family and identified 6 non-synonymous mutations within AP2-06B (PF3D7_0613800), with allele frequencies greater than 0.05. One mutation, K3124R, was located in a PfAP2-06B AP2 domain.MethodsTo investigate transcriptional regulation by PfAP2-06B, ChIP-seq assays were performed on 3D7/PfAP2-06B-GFP schizonts using antibodies against GFP. The DNA sequences of the artemisinin-resistant CWX and the quinoline-resistant strains PfDd2 and Pf7G8 were analyzed for the genetic diversity of AP2-06B, compared with the Pf3D7 strain as a reference sequence. To determine whether AP2-06B can alter the expression of pfk13 and pfcrt, as well as cause artemisinin and quinoline resistance in Plasmodium, we generated both a K3124R mutation and conditional knockdown of AP2-06B in Pf3D7 using CRISPR/Cas9-mediated genome editing.ResultsChIP-Seq analysis showed that AP2-06B can bind to the loci of the Plasmodium genes pfk13 and pfcrt. The AP2-06B K3124R mutation was also found in the artemisinin-resistant parasite strain CWX and the chloroquine-resistant strains Dd2 and 7G8. Contrary to expectation, Pf3D7 Plasmodium lines modified by either K3124R mutation of AP2-06B or conditional knockdown of AP2-06B did not have altered sensitivity to artemisinin or quinolines by modulating pfk13 or pfcrt expression.DiscussionAP2-06B was predicted to be associated with artemisinin and quinoline resistance, but no change in resistance was observed after mutation or conditional knockdown. Given the multigenic nature of resistance, it might be difficult to recreate a resistance phenotype. In conclusion, whether AP2-06B regulates the development of artemisinin or quinoline resistance remains to be studied.